Interactions among biocontrol agents in the management of Lycoriella ingenua and Trichoderma aggressivum on white button mushrooms - Luković, Jelena; Milijašević-Marčić, Svetlana; Šantrić, Ljiljana; Drobnjaković, Tanja; Anđelković, Nikola; Grujić, Nikola; Potočnik, Ivana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2026)
Relationships (synergistic/antagonistic/additive) among three biocontrol agents — the native antagonistic bacterium Bacillus amyloliquefaciens B-241, the yield-stimulating actinobacterium Streptomyces flavovirens A06, and a commercial strain of entomopathogenic nematode Steinernema feltiae — were investigated for the purpose of evaluating their effects on the suppression of artificially inoculated green mould disease agent Trichoderma aggressivum f. europaeum T77, as well as the suppression of natural infestation of the fungus gnat, Lycoriella ingenua, in an experimental growing chamber of cultivated white button mushroom Agaricus bisporus. Biocontrol agents were applied at standard application rates, or reduced rates of 40% or 20%. The impact of biocontrol agents and their interactions on mushroom productivity was calculated as the ratio of the fresh weight of the total mushroom yield to the weight of the dry spawned substrate. The density of the fungus gnat flies was monitored by using yellow sticky traps placed inside each insect-rearing cage with mushroom substrate. The evaluation of disease and pest control efficacy was based on disease and pest incidence in the inoculated control and treatment groups. Simultaneous application of three biocontrol agents revealed mild antagonistic interactions in their efficacy in green mould disease control, an antagonistic relationship in the control of the fungus gnat, while synergy was detected regarding their impact on mushroom yield. The results of this study suggest that each biological agent should be applied three times every seven days to provide efficient pest and disease control: entomopathogenic nematodes used individually at the first day after the casing time (S. feltiae 0.75 × 106 IJ m-2, total amount 2.25 × 106 IJ m-2), and beneficial microorganisms used combined a few days later (B. amyloliquefaciens 1 × 109 CFU ml-1 m-2, total amount 3 × 109 CFU ml-1 m-2, and S. flavovirens 1 × 108 CFU ml-1 m-2, total amount 3 × 108 CFU ml-1 m-2).